Pengaruh Pendidikan Kesehatan Kanker Payudara Metode Peer Group Terhadap Tingkat Pengetahuan Sikap dan Perilaku SADARI Ibu-Ibu PKK Kelurahan Karangasem - Prabarini, Lintang Puspita; , H.M Abi Muhlisin., SKM. M.KEP (2017)
Breast cancer is the uncontrolled growth of cells that occur in the breast and can spread goto the other side of body. Breast cancer is the most frequently diagnosed cancer of women in the worldwide and occupy the number two cause of death in Indonesia with a percentage of 43%. Increasing age in women is one of the most important risk factor for breast cancer. Breast self-examination is one of the easiest ways to detect breast cancer. Lack of knowledge about breast cancer and BSE causing many women late to diagnosed and get treatment. The purpose of this study is to determine the effect of health education on the level of knowledge, attitudes and behavior of women in childbearing age about breast cancer and BSE. Material and Methods : This research using pra experimental design, with one group pretest posttest approach to 30 women with age range between 20-50 years old. The level of knowledge and attitude was measured by using structured validated questionnaire, 20 item for knowledge and 1-0 items fot attitude. While behavior was measured by using the observational sheet of BSE. From pretest we know that only 23,3% responden have good knowledge, while 67,7% responden in categories medium. On the attitude indicator 63,3% responden have less attitude, while the other have a good attitude. From this study known that all respondents have less ability and behavior about breast self-examination. After given health education, posttest result show improvement in knowledge indicator, that is 86,7% have good knowledge, and 13,3% have medium knowledge. Attitude indicator, posttest result shows 83,3% respondent have good attitude, and 16,7% have medium attitude. Ten people or 33,3% of respondent have improvement ability and behavior to be good. Fromthe results of this study it is known that health education has an influence on increasing knowledge, attitude, and behavior of respondents.